Pengambilan Lantanum dan Nikel dari Katalis Bekas Menggunakan Asam Sitrat: Peninjauan Performa secara Kuantitatif Menggunakan Response Surface Method (Lantanum and Nickel Recovery from Spent Catalyst Using Citric Acid : Quantitative Performance......) - Himawan Tri Bayu Murti Petrus; Ardyanto Wijaya; Yusuf Iskandar; Danu Bratakusuma; Hendrik Setiawan; Wiratni Wiratni; Widi Astuti (National Research and Innovation Agency (BRIN), 2018)
Heavy metals and Rare earth elements (REEs) are nowadays being used widely in many industries from electronics to petroleum industries as catalysts. However, their disposal caused serious problems to the environment. With the sharp growth in its usage, there is a better way to use and utilize valuable metals from secondary sources such as their disposal rather than using new raw materials. The aim of this work is to study the potential of citric acid as a leaching agent to extract lanthanum and nickel in various acid concentration and leaching temperature. The raw material used in this work is spent catalyst from Pertamina Refinery Unit VI, Balongan, Indonesia. The spent catalyst is decarbonized with a heat treatment at 725°C for 10 minutes before the leaching process. The leaching process used 0.1; 1; and 2 M of citric acid with a varied temperature of 30, 60, and 80°C. The lanthanum recovery was calculated by comparing the mass percentage of lanthanum before leaching process and after leaching process using Energy Dispersive X-Ray Spectroscopy (EDX). The results were analyzed by response surface methodology (RSM) and are proved to be a reliable method to depict and analyze the leaching characteristics. The molarity of the citric acid is the most significant independent variables used in the research for lanthanum recovery response. However, based on the Pareto analysis result there are no significant variables that affect the recovery of nickel. The second order polynomial fitting model is also proved to be compatible with the response of lanthanum recovery but is less compatible with nickel recovery. AbstrakPengambilan logam tanah jarang dan logam berat dari sumber sekunder (katalis bekas, limbah padat industri, dan abu terbang) menjadi alternatif karena pertimbangan lingkungan dan ketersediaan bijih di alam yang semakin sedikit. Pertimbangan tersebut yang mendasari studi tentang pengambilan lantanum dan nikel dari katalis bekas dengan menggunakan asam asetat. Bahan untuk penelitian ini adalah katalis bekas dari Penyulingan Pertamina Unit VI, Balongan. Sebelum pelindian dilakukan, katalis bekas didekarbonasi dengan perlakuan panas pada 725 °C selama 10 menit. Proses pelindian dilakukan dengan memvariasikan suhu dan konsentrasi asam asetat. Hasil eksperimen ditinjau menggunakanRSM (response surface methodology) dan terbukti sebagai metode yang dapat diandalkan untuk menggambarkan dan menganalisis karakter proses pelindian. Molaritas asam merupakan variabel independen yang secara signifikan mempengaruhi respon dalam pengambilan lantanum. Walaupun begitu, berdasarkan hasil analisis Pareto, tidak ada variabel yang secara signifikan mempengaruhi pengambilan nikel. Model fitting polinomial orde dua juga terbukti cocok dengan respon proses pengambilan lantanum daripada nikel. Hasil RSM menunjukkan bahwa kondisi optimum dari ekstraksilantanum dan nikel adalah pada pH 2 dan suhu 45 оC dimana lantanum dapat 100% terambil dan nikel sebanyak 60%.